In situ TREXS Observation of Surface Reduction Reaction of NiO Film with ∼2 nm Surface Sensitivity. Issue 7 (28th March 2019) - Abe, Hitoshi; Niwa, Yasuhiro; Takeichi, Yasuo; Kimura, Masao
Abstract: X‐ray absorption fine structure (XAFS) spectroscopy is one of the most widely used methods at synchrotron radiation facilities. XAFS gives us information on chemical states and local structures. Fundamentally, XAFS is bulk sensitive, not surface sensitive. If a surface sensitive XAFS method was available, surface chemical reactions can be observed under realistic conditions. Here, we report the development and present status of a type of surface sensitive x‐ray spectroscopy, which is named total reflection x‐ray spectroscopy, TREXS. Abstract : Total REflection X‐ray Spcetroscopy (TREXS) captures surfaces with the surface sensitivity of ∼2 nm.